Neuroinflammation in pathogenesis of Alzheimer's disease: Phytochemicals as potential therapeutics. (July 2020) - Vaiserman, Alexander; Koliada, Alexander; Lushchak, Oleh
Highlights: Inflammation and vascular dysfunction play important roles in Alzheimer's disease. Phytobioactive compounds have potent antioxidant and anti-inflammatory properties. Therefore, they have potential to be promising anti-Alzheimer's therapeutics. Abstract: Accumulation of neurotoxic forms of amyloid-β proteins in senile plaques and hyperphosphorylated tau proteins in neurofibrillary tangles is a well-known pathophysiological hallmark of Alzheimer's disease (AD). However, clinical trials with drugs targeting amyloid-β and tau have failed to demonstrate efficacy in treating AD. All currently FDA-approved anti-AD drugs have symptomatic effects only and are not able to cure this disease. This makes necessary to search for alternative therapeutic targets. Accumulating evidence suggests that systemic inflammation and related vascular dysfunction play important etiological roles in AD and precede its clinical manifestation. Therefore, novel therapeutic modalities targeted at these pathophysiological components of AD are intensively developed now. Phytochemicals such as resveratrol, curcumin, quercetin, genistein and catechins are promising anti-AD therapeutics due to their ability to affect major pathogenetic mechanisms of AD, including oxidative stress, neuroinflammation and mitochondrial dysfunction. The implementation of innovative approaches for phytochemical delivery, including the nanotechnology-based ones which enable to significantly enhance their oral bioavailability, would likely provide an opportunity to address many challenges of conventional anti-AD therapies. In this review, roles of inflammation and vascular dysregulation in AD are described and phytobioactive compound-based treatment strategies for AD are discussed.